Transformation of zinc and iron in submerged rice soils of Kashmir - WANI, MUSHTAQ A; BHAT, M A; KIRMANI, N A; NAZIR, SHAISTA (The Indian Journal of Agricultural Sciences, 2026)
Thirty five alluvial rice (Oryza sativa L.) growing soils of Kashmir (India) were studied for transformation and distribution of different forms of Zn and Fe on submergence out of forty soils. The results revealed that more than 83% of total Zn occurred in the relatively inactive clay lattice-bound form while a smaller fraction, viz. 1.09, 1.82, 11.70 and 2.27% of the total zinc occurred as water-soluble plus exchangeable, organic complexed, amorphous sesquioxide-bound and crystalline sesquioxide bound forms, respectively. All these four Zn forms showed significant negative correlations with soil pH (r = –0.637**, –0.419*, –0.539** and –0.528**, respectively), while the latter two Zn forms showed significant positive correlations with Fe2O3(r = 0.510** and 0.540**)and A12O3 (r = 0.698** and 0.536**) content of the soils. The different Zn forms were found to have positive and significant correlations amongst each other, suggesting the existence of a dynamic equilibrium of these forms in soil. There was a marked increase in NH4OAc and AlCl3 extractable Fe with concomitant decrease in CBD-Fe. Much of Fe3+ in crystalline sesquioxides underwent dissolution due to reduction to Fe2+.